2021
DOI: 10.1186/s12884-021-04190-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin administration for induction and augmentation of labour in polish maternity units – an observational study

Abstract: Background There is not enough data regarding practices and protocols on the dose of oxytocin administrated to women during labour. Empirical evidence indicates that compliance with the guidelines improves the quality of healthcare and reduces adverse effects. The study aimed to evaluate practices of oxytocin provision for labour induction and augmentation in two maternity units in Poland. Methods The article presents a prospective observational st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
(37 reference statements)
1
9
0
Order By: Relevance
“…French researchers Girault et al showed that the determinants of abuse of augmentation of labor were, among others, epidural anesthesia [ 21 ]. Baranowska et al observed a correlation between the average cumulative dose of oxytocin administered during labor and the use of epidural anesthesia [ 22 ]. Other researchers came to similar conclusions, both in terms of more frequent use of oxytocin after the start of epidural anesthesia [ 23 , 24 ] and more frequent use of epidural anesthesia after the augmentation of labor with oxytocin [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…French researchers Girault et al showed that the determinants of abuse of augmentation of labor were, among others, epidural anesthesia [ 21 ]. Baranowska et al observed a correlation between the average cumulative dose of oxytocin administered during labor and the use of epidural anesthesia [ 22 ]. Other researchers came to similar conclusions, both in terms of more frequent use of oxytocin after the start of epidural anesthesia [ 23 , 24 ] and more frequent use of epidural anesthesia after the augmentation of labor with oxytocin [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers came to similar conclusions, both in terms of more frequent use of oxytocin after the start of epidural anesthesia [ 23 , 24 ] and more frequent use of epidural anesthesia after the augmentation of labor with oxytocin [ 25 , 26 ]. To some extent, this can be explained by more painful contractions that are stimulated by oxytocin and movement limitations caused by the required continuous CTG recording during the stimulation of uterine contractions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is secreted when triggered by labour, lactation, social interaction, and stressors. Oxytocin acts on the myometrium to induce uterine contractions via G-proteins with the subsequent release of intracellular calcium stores through a complex interplay on its activity on phospholipase C. Its potency is directly proportional with advancing gestational age when there are sufficient oxytocin receptors [43]. The synthetic oxytocin is a cyclic nonapeptide which is identical to the natural oxytocin obtained via chemical synthesis.…”
Section: Oxytocinmentioning
confidence: 99%
“…Oxytocin is one of the most used drugs in delivery rooms, used to induce or stimulate childbirth, which is the subject of interest to researchers around the world [37][38][39]. Nakai et al (2006) conducted studies to learn about the incidence and risk factors of severe perineal trauma in Japanese patients.…”
Section: Resultsmentioning
confidence: 99%